Effects of MHRA drug safety advice on time trends in prescribing volume and indices of clinical toxicity for quinine. (December 2013) - Acheampong, Paul; Cooper, Gill; Khazaeli, Behshad; Lupton, David J.; White, Sue; May, Margaret T.; Thomas, Simon H. L.
<x xml:space="preserve">Abstract</x> Aims To ascertain the effects of the Medicines and Healthcare products Regulatory Agency's (MHRA) safety update in June 2010 on the volume of prescribing of quinine and on indices of quinine toxicity. Methods We analysed quarterly primary care total and quinine prescribing data for England and quinine prescribing volume for individual Primary Care Trusts in the North East of England from 2007/8 to 2011/12 obtained from the ePACT.net database. We also analysed quinine toxicity enquiries to the National Poisons Information Service (NPIS) via Toxbase® and by telephone between 2004/5 and 2011/12. Joinpoint regression and Pearson's correlation tests were used to ascertain changes in trends in prescribing and indices of toxicity and associations between prescribing and indices of toxicity, respectively. Results Total prescribing continued to increase, but annual growth in quinine prescribing in England declined from 6.0 to −0.6% following the MHRA update [difference −0.04 (95% confidence interval −0.07 to −0.01) quinine prescriptions per 100 patients per quarter, P = 0.0111]. Much larger reductions were observed in Primary Care Trusts that introduced comprehensive prescribing reviews. The previously increasing trend in Toxbase® quinine searches was reversed [difference −19.76 (95% confidence interval −39.28 to −9.20) user sessions per quarter, P = 0.0575]. Telephone enquiries to NPIS for quinine have declined, with stabilization of the proportion of moderate to severe cases of quinine poisoning since the update. Conclusions The MHRA advice was followed by limited reductions in the growth in quinine prescribing and in indicators of quinine overdose and toxicity. Quinine prescribing, however, remains common, and further efforts are needed to reduce availability and use.